DISPOSITION DIAGNOSTIC MEANS OF DEFENSIVE AND COPING BEHAVIOR IN THE EDUCATIONAL ENVIRONMENT - Anna D. Boyko (Russian State Vocational Pedagogical University, 2015)
Educational environment today is one of the most effective mediums for self-development and acquisition of new competencies. But due to its structural complexity this environment is highly stressful. However, up to now there are no procedures that would diagnose complex formations (eg, disposition) of the defensive and coping behavior in the educational environment. Therefore, the aim of this investigation is to close this gap.Methods. After analyzing the existing problems of the theoretical aspects of psychological defense mechanisms of defensive and coping behavior, and taking as a basis the theory of protective dispositions and coping behavior different ways were allocated to show these dispositions in the educational environment.Scientific novelty. The personality questionnaire «Dispositions of defensive and coping behavior in the educational environment» is designed. This questionnaire has sufficient level of validity and reliability. A total of 402 people took part herein the study including different stages.Practical significance. The ready-made questionnaire can be applied by teachers who want to improve the quality of educational process. It will also be useful for students seeking to understand and eliminate the possible cause of own difficulties encountered while studying.